Voice of the customer - Dutka, Alan (Henry Stewart Talks, 2008)
Listening to customers is the primary method for measuring and tracking satisfaction, Wide variety of techniques used to gather and analyze this information, Sample development, Questionnaire design, Administration, Analysis and interpretation of results, How to avoid mistakes and pitfalls